A study on pregnancy outcome following previous one spontaneous abortion - Chandna, Archana; Sood, Anoopa; Mittal, Rita; Soni, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy plays a unique role in the transformation of women towards completeness. Pregnancy should be considered a unique normal physiological episode in a woman’s life. However in some cases many twists and turns occur which alter the good outcome of pregnancy into a disaster. For those women who have had a previous unsuccessful outcome, pregnancy may bring a lot of inevitable negative emotions. The main objective of our study was to determine pregnancy outcome following previous one spontaneous abortion Methods: A prospective study was done on 756 patients. There were 252 patients in the case group consisting of pregnant females with the history of previous one spontaneous abortion (group A). There were two control groups - primigravida women (group B) & second gravida with history of previous successful pregnancy outcome (group C) who delivered subsequent to our study group. All the antenatal, post natal complications and modes of delivery were noted and compared between the three groups. Results: Pregnancy complications included: threatened miscarriage, premature rupture of membranes (PROM), preterm delivery, intra uterine growth restriction (IUGR), diabetes mellitus, abruption, placenta praevia, preeclampsia, eclampsia and postpartum hemorrhage (PPH). Statistical analysis was carried out using Statistical Package for Social Scientists (SPSS) version 20. Statistical analysis showed that all the complications except preeclampsia, eclampsia, placenta praevia and diabetes were more in the study group than both the control groups (p<0.05). Risk of preeclampsia was more in primigravidae. Rate of caesarean section and instrumental delivery was also significantly increased in women with previous one spontaneous abortion. Conclusions: Women with a history of previous one spontaneous abortion are at an increased risk of complications in the next pregnancy. So careful surveillance should be provided to such women and not to be restricted only to females with history of recurrent pregnancy loss.